2009
DOI: 10.1017/s0950268809002490
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for severe community-associated methicillin-resistant Staphylococcus aureus infection

Abstract: Community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) has rapidly emerged in the USA as a cause of severe infections in previously healthy persons without traditional risk factors. We describe the epidemiology of severe CA-MRSA disease in the state of Georgia, USA and analyse the risk of death associated with three different clinical syndromes of CA-MRSA disease - pneumonia, invasive disease, and skin and soft-tissue infections (SSTIs). A total of 1670 cases of severe CA-MRSA disease were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 5 publications
3
16
0
1
Order By: Relevance
“…Another study showed an increase in S. aureus bacteraemia during the 2009–2010 pandemic H1N1 seasons (compared with influenza seasons in previous years) but not during the regular influenza seasons of 2006–2009 (when compared with other seasons of the year) [35]. Seasonal variation in mortality from S. aureus infection was assessed in two studies; both studies found a higher mortality in winter [21,38].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed an increase in S. aureus bacteraemia during the 2009–2010 pandemic H1N1 seasons (compared with influenza seasons in previous years) but not during the regular influenza seasons of 2006–2009 (when compared with other seasons of the year) [35]. Seasonal variation in mortality from S. aureus infection was assessed in two studies; both studies found a higher mortality in winter [21,38].…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 13 studies were performed with the specific objective of assessing S. aureus seasonality [4,9,[11][12][13][14]16,18,22,28,30,34,35] and the remaining studies assessed seasonal occurrence as a secondary objective. There were 13 multi-centre studies [7][8][9]11,15,18,21,24,31,35,36,38,41] and the remaining studies were performed at a single institution.…”
Section: Quality Of the Literaturementioning
confidence: 99%
“…Patients with necrotizing CA-MRSA pneumonia present with hemoptysis, leukopenia, high fever and cavitary lung lesions (22). These patients have an odds ratio of dying of 11.3 (95% CI, 5.6 to 23) compared to other severe CA-MRSA infections (1, 23). One study reported a 56% mortality rate for CA-MRSA pneumonia with a median age of 14.5 (1, 24).…”
Section: Resistant Pathogens and Fungimentioning
confidence: 96%
“…aureus is the most significant nosocomial pathogen, and methicillin-resistant S. aureus strains, which caused approximately 19,000 deaths in 2005 in the United States (2, 11), have recently emerged in the community, causing an inordinate number of skin and soft tissue infections in otherwise healthy populations (13,15).…”
mentioning
confidence: 99%